Notas sobre las transformaciones psíquicas de la adolescencia en la historia del psicoanálisis (2004)
ABSTRACT: The determinism of childhood captured the attention of psychoanalytic thought and overshadowed the crucial role of adolescence, which Freud himself recognized. New approaches to the specificity and importance of adolescence begin to crop up in the mid-twentieth century, supported in clinical practice with adolescents developed after WWII. Finally the integration of the concept of "afterwards" Nachträglichkeit in these theories best validates the thesis that adolescent psychic transformations are not confined to the recapitulation of previous problems.